The mediation of perceived external marketability between self-direction and intention to quit among teachers - Hira, Khan (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2020)
Link to publisher's homepage at https://ijbt.unimap.edu.my